Language and Ideal Thought in the Philosophical Teaching of Suphasit Phra Ruang - Pimpuang, Kowit; Yuttapongtada, Methawee (Journal of International Studies, Prince of Songkla University, 2018)
The research aimed to explore the language and ideal thought in the philosophical teaching of Suphasit Phra Ruang. The objectives of this study were dealt mainly 1) to explore the language aspect used in the philosophical teaching of Suphasit Phra Ruang; 2) to explore the word formation and sound and sematic changes of the loanwords found in the philosophical teaching of Suphasit Phra Ruang; and 3) to explore the ideal thought in the philosophical teaching of Suphasit Phra Ruang. It was found that most short and simple words were applied compactly in the forms of reduplication words, compound words, comparative words, rhyming words and playing with words. Each Vagga contained approximately 5-6 words and often ended completely within one Vagga or no more two Vaggas. Moreover, it was found that Khmer followed by Pali-Sanskrit were loanwords in different Vaggas. Particularly, the word formation of Pali-Sanskrit according to the following forms; Primary Derivative (Kitaka), Compound (Samasa), Secondary Derivative (Tathita) and Prefix (Upasagga) was found obviously. These loanwords were changed through the thorough sound change system namely; insertion, deletion and changes of sound. Not only that, they also were changed through the semantic change system namely; widening of meaning, narrowing of meaning and transferring of meaning. As for the study on the ideal thought in the philosophical teaching of Suphasit Phra Ruang, it was found that there were the obvious and simple ideal thoughts related to the principle of doctrines in Buddhism.